STING-targeting PROTACs: emerging therapeutic tools for enhanced immunotherapy in inflammatory diseases - Jiang, Wenqing; Yang, Xiaoping; Liu, Huiying; Wang, Chao; Niu, Hongxin; Yu, Wanpeng (Frontiers in Immunology, 2025)
The stimulator of interferon genes (STING) pathway is a central regulator of innate immunity, mediating host defense against pathogens but driving chronic inflammation when dysregulated-underpinning autoimmune diseases, fibrosis, and cancer. Traditional therapies targeting STING (e.g., small-molecule inhibitors, monoclonal antibodies) face limitations including incomplete pathway suppression, off-target effects, and reliance on continuous dosing. Proteolysis-targeting chimeras (PROTACs) offer a transformative approach by enabling selective degradation of STING, achieving sustained suppression of pathological signaling. However, critical gaps remain in understanding their selectivity for pathological vs. homeostatic STING activity, risks of immune suppression, and translational challenges. This review critically evaluates the rationale for STING degradation, with a comparative analysis of recent PROTAC designs (including warhead, E3 ligase, and linker optimization) and their pharmacokinetic/pharmacodynamic trade-offs. We address compensatory innate immune pathways, biomarker development hurdles, and safety risks, highlighting strategies to enhance specificity and clinical utility. STING-targeting PROTACs hold promise for inflammatory diseases, but their success depends on overcoming these challenges.